2014
DOI: 10.26719/2014.20.8.491
|View full text |Cite
|
Sign up to set email alerts
|

Seat-belt use among drivers and front passengers: an observational study from the Islamic Republic of Iran

Abstract: Although seat-belts are the most effective means of preventing severe injuries and deaths from road accidents, drivers and passengers in many developing countries neglect to wear them. This study aimed to measure the rate of use of seat-belts and factors affecting their use in Tehran, Islamic Republic of Iran. In direct observations of 7718 vehicles at randomly selected sites in Tehran, 77.9% of drivers and 43.7% of front passenger had seat-belts fastened. More women used seat-belts than did men while driving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 21 publications
2
14
0
1
Order By: Relevance
“…This could be related to a higher level of traffic law enforcement and a stronger safe driving culture in Kashmar. However, in agreement with previous Iranian research, the results of the current study showed that female drivers wore seat belts more often than males (Borghebani et al, 2012, Sadeghnejad et al, 2014, Nabipour et al, 2014. This was to be expected as this finding has also been reported in other countries (Nabipour et al, 2014, Afukaar et al, 2010, Crandon et al, 2006, Popoola et al, 2013, Ma et al, 2012, Ipingbemi, 2012, Olukoga et al, 2011, Crandon et al, 1996.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…This could be related to a higher level of traffic law enforcement and a stronger safe driving culture in Kashmar. However, in agreement with previous Iranian research, the results of the current study showed that female drivers wore seat belts more often than males (Borghebani et al, 2012, Sadeghnejad et al, 2014, Nabipour et al, 2014. This was to be expected as this finding has also been reported in other countries (Nabipour et al, 2014, Afukaar et al, 2010, Crandon et al, 2006, Popoola et al, 2013, Ma et al, 2012, Ipingbemi, 2012, Olukoga et al, 2011, Crandon et al, 1996.…”
Section: Resultssupporting
confidence: 94%
“…Further, in Khalilabad and Bardaskan private car drivers wore a seat belt more often than those in the -other‖ group. This is supported by previous research in Tehran, which also found that taxi drivers used seat belts more frequently than those driving private cars, vans, or pickup trucks (Sadeghnejad et al, 2014). Furthermore, observational research in Nigeria showed that seat belt fastening among drivers of private cars and taxis were both higher than bus drivers (Iribhogbe and Osime, 2008).…”
Section: Resultsmentioning
confidence: 50%
See 3 more Smart Citations